TOXICOLOGICAL EVALUATION OF CHLORPYRIFOS AND NEEM EXTRACT (BIOSAL B) AGAINST 3RD INSTARS LARVAE OF DROSOPHILA MELANOGASTER - S. I. Anjum; M. J. Yousf; S. Ayaz; B. S. Siddiqui (Journal of Animal and Plant Sciences, 2010)
Third instars larvae of Drosophila melanogaster were assessed for toxicological evaluation of Chlorpyrifos and Neem extract. The larvae were found to be melanized and failed to pupate when both the compounds were applied. Lethal concentration (LC50 ) of chlorpyrifos (40EC) 0.0127% and of neem extract (Biosal B) were found to be 2.4%. LC50, were determined to be higher in Neem extract as compared to chlorpyrifos. Treatment of Drosophila with chlorpyrifos and Neem extract suggested that chlorpyrifos is very effective pesticide than Neem extract. Further, the melanization and antifeedent activity revealed that Neem extract may affect up to hormonal level of insect.Both compounds were found to inhibit the level of cholinesterase in treated insects as compared to control.
Keywords: Chlorpyrifos; Cholinesterase; Drosophila melanogaster; Neem extract; Toxicity